Noorda esmeralda (HAMPS.) (LEPIDOPTERA, PYRALIDAE), LAGARTA DOS FRUTOS DO GUATAMBU, Aspidosperma ramiflorum M. ARG,. (APOCYNACEAE) - Cerignoni, JoÃ£o Angelo; Berti Filho, Evoneo; Vieira, Israel Gomes (REVISTA DE AGRICULTURA, 2015)
Noorda esmeralda (HAMPS.) (LEPIDOPTERA, PYRALIDAE), LAGARTA DOS FRUTOS DO GUATAMBU, Aspidosperma ramiflorum M. ARG,. (APOCYNACEAE)